1999
DOI: 10.1046/j.1365-2958.1999.01659.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicase motifs: the engine that powers DNA unwinding

Abstract: SummaryHelicases play essential roles in nearly all DNA metabolic transactions and have been implicated in a variety of human genetic disorders. A hallmark of these enzymes is the existence of a set of highly conserved amino acid sequences termed the`helicase motifs' that were hypothesized to be critical for helicase function. These motifs are shared by another group of enzymes involved in chromatin remodelling. Numerous structure±function studies, targeting highly conserved residues within the helicase motifs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
298
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(311 citation statements)
references
References 59 publications
9
298
0
1
Order By: Relevance
“…The amino acid sequences of the Cas3 proteins contain the seven motifs that are characteristic for the superfamily 2 of the helicases, proteins that power DNA unwinding. Homologues of this superfamily may have functions in DNA repair, transcriptional regulation, chromosome segregation, recombination and chromatin remodelling (Hall and Matson, 1999). The Cas4 proteins showed similarity to RecB exonucleases.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid sequences of the Cas3 proteins contain the seven motifs that are characteristic for the superfamily 2 of the helicases, proteins that power DNA unwinding. Homologues of this superfamily may have functions in DNA repair, transcriptional regulation, chromosome segregation, recombination and chromatin remodelling (Hall and Matson, 1999). The Cas4 proteins showed similarity to RecB exonucleases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this region is 27% identical to TraA relaxase/helicase encoded by the Agrobacterium tumefaciens pTiC58 plasmid (Farrand et al, 1996), and 22% identical to the TraI relaxase/helicase of the E. coli F factor (AbdelMonem et al, 1983;Larkin et al, 2005;Street et al, 2003). Alignments to the consensus helicase motifs (Hall and Matson, 1999) revealed that pREA400 TraA and its actinomycete relatives belong to the superfamily I (SFI) type of helicases (Fig. 3A).…”
Section: Sequence Analysis Of Prea400 Encoded Traamentioning
confidence: 97%
“…Protein alignments of DNA helicase and relaxase domains of pREA400 TraA. (A) Alignments of actinomycete transfer proteins from the indicated strains or plasmids to the consensus motifs (I, IA, II, III, IV, V, and VI) of superfamily I-type helicases (Hall and Matson, 1999). Consensus hydrophobic, hydrophilic and non-speciWc helicase residues are indicated with +, o, and x, respectively.…”
Section: Targeted Gene Disruption Of Traamentioning
confidence: 99%
“…This motif, DExx, is involved in NTP hydrolysis [46,76,86]. The D and E residues coordinate the ATP-associated Mg 2+ and activate the attacking water molecule, respectively [109,110].…”
Section: Motif II (Walker B) [108]mentioning
confidence: 99%